Forming of educational material in adaptive system of knowledge transfer - Федорук, Павло Іванович; Петрик, Сергій Михайлович (Eastern-European Journal of Enterprise Technologies, 2011)
The article reveals the method of knowledge representation in adaptive system of knowledge transfer, which allows operating different by structure parts of learning material for providing the process of individual learning. Mathematical model of the method and features of its use are described